2018
DOI: 10.1038/s41396-018-0107-z
|View full text |Cite
|
Sign up to set email alerts
|

Life on the edge: active microbial communities in the Kryos MgCl2-brine basin at very low water activity

Abstract: The Kryos Basin is a deep-sea hypersaline anoxic basin (DHAB) located in the Eastern Mediterranean Sea (34.98°N 22.04°E). It is filled with brine of re-dissolved Messinian evaporites and is nearly saturated with MgCl-equivalents, which makes this habitat extremely challenging for life. The strong density difference between the anoxic brine and the overlying oxic Mediterranean seawater impedes mixing, giving rise to a narrow chemocline. Here, we investigate the microbial community structure and activities acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 96 publications
(163 reference statements)
3
50
0
Order By: Relevance
“…The reduction in water availability in hypersaline environments represents a fundamental stress for cellular systems (Hallsworth et al, ). The lowest a w value for growth recorded to date is 0.4 (Steinle et al, ). In this study, we observed that natural brine displayed values of a w of 0.74.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in water availability in hypersaline environments represents a fundamental stress for cellular systems (Hallsworth et al, ). The lowest a w value for growth recorded to date is 0.4 (Steinle et al, ). In this study, we observed that natural brine displayed values of a w of 0.74.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid biomarkers were extracted and analyzed according to previously reported protocols (Elvert et al, 2003) with modification for alcohol derivatization (Niemann et al, 2005) and instrument setup (Blees et al, 2014;Steinle et al, 2018). Briefly, a total lipid extract (TLE) was obtained by ultrasonication of ∼ 20 g wet sediment samples in four extraction steps with solvents of decreasing polarity: dichloromethane (DCM) / methanol (MeOH) 1 : 2; DCM/MeOH 2 : 1; and DCM for the last two extraction steps.…”
Section: Lipid Extraction Quantification Identification and Determmentioning
confidence: 99%
“…Identities, concentrations, and stable carbon isotope composition of individual compounds were determined with a gas chromatograph linked to a quadrupole mass spectrometer, flame‐ionization detector, or an isotope ratio mass spectrometer, respectively, as described in Steinle et al (2018). Concentrations were calculated using the internal standard.…”
Section: Methodsmentioning
confidence: 99%